Complete genome of a methicillin-resistant Staphylococcus vitulinus from Danish ground beef meat carrying a mecA2 resistance gene and a novel ccr allotype. (December 2020) - Looman, Esmée Lauren; van Tienen, Paula; Ng, Duncan Y.K.; Baig, Sharmin; Fait, Anaëlle; Overballe-Petersen, Søren; Andersen, Paal S.; Stegger, Marc
Abstract: Objectives: To report the complete genome sequence of a methicillin-resistant Staphylococcus vitulinus from ground beef to allow comparison with other available S. vitulinus genomes and to investigate its SCC mec element. Methods: Meat samples from grocery stores in Denmark were examined for the presence of staphylococcal species by plating on selective plates. One colony isolated from beef was identified as S . vitulinus by MALDI-TOF and genome sequenced using a combination of Illumina and Oxford Nanopore technologies. Phylogenetic and in silico resistome analyses were performed for all available S. vitulinus genomes. Results: The closed genome of S. vitulinus Tienloo1 isolate had a chromosome size of 2, 628, 028 bp and contained a single novel 2, 380 bp plasmid based on a hybrid assembly. It carried mecA as the only resistance marker. The isolate was found not to carry any immune evasion cluster genes, which have been putatively associated to human origin. Comparison with all publicly available S. vitulinus draft genomes showed a diverse population and revealed that only the Danish beef isolate contained a mec gene in addition to a ccr gene complex. Additionally, the single ccrC gene within the isolate was novel and distant from the mecA2 gene. Conclusion: This isolate, Tienloo1, from a ground beef meat sample represents the first complete genome of S. vitulinus found to carry a mecA2 gene and a novel ccr allotype in its SCC mec element that is distinct from all publicly available draft S. vitulinus genomes.